2019
DOI: 10.1177/2165079919829154
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Outside the Workplace, Coping Styles, and Burnout in a Cohort of EMS Providers From Minnesota

Abstract: Occupational burnout has been linked to the delivery of lower quality of care in some health care professions, including with turnover intentions and absenteeism in emergency medical services (EMS) workers. Thus, studies that identify factors associated with burnout may be integral to optimizing quality and workforce engagement among EMS professionals. A survey was conducted to assess social support outside the workplace, coping styles, and occupational burnout in a cohort of EMS providers from Minnesota. Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 47 publications
5
24
0
3
Order By: Relevance
“…Cañadas-De la Fuente et al (2015) stated that healthcare settings, including paramedic disciplines, are highly exposed to burnout through exposure to emotionally traumatic incidents, patient deaths, as well as other incidents that cause burnout. Boland et al (2019) found that female paramedics had higher emotional expression than male paramedics, especially in challenging situations, which is supported by the data in the current study. However, this may not necessarily be the case, as a recent Saudi study reported that 82.6% of male Saudi Arabian paramedics were exposed to burnout and looked forward to being off duty (Almutairi and Mahalli, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Cañadas-De la Fuente et al (2015) stated that healthcare settings, including paramedic disciplines, are highly exposed to burnout through exposure to emotionally traumatic incidents, patient deaths, as well as other incidents that cause burnout. Boland et al (2019) found that female paramedics had higher emotional expression than male paramedics, especially in challenging situations, which is supported by the data in the current study. However, this may not necessarily be the case, as a recent Saudi study reported that 82.6% of male Saudi Arabian paramedics were exposed to burnout and looked forward to being off duty (Almutairi and Mahalli, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Seeking support in their own social network has been reported, although this study also reported on ambulance care professionals feeling misunderstood by their social network [ 19 ]. When social support is lacking, ambulance care professionals face increased risks for psychological consequences [ 29 ]. To optimize support as coping style in the EMS organization, peer supporters could be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of students, social support was associated with resilience to stress (Park et al 2015 ). In contrast, low social support outside the workplace was associated with more burnout (Boland et al 2019 ). Resilience and social support were not investigated in this study, which is a limitation.…”
Section: Discussionmentioning
confidence: 99%